2018
DOI: 10.1182/bloodadvances.2018016964
|View full text |Cite
|
Sign up to set email alerts
|

Similar telomere attrition rates in androgen-treated and untreated patients with dyskeratosis congenita

Abstract: Dyskeratosis congenita (DC) is an inherited bone marrow failure syndrome and the prototypic telomere biology disorder (TBD). Leukocyte telomere length (TL) less than the first percentile for age, measured by flow cytometry with in situ hybridization (flow FISH), is diagnostic of DC. Androgens are a therapeutic option for DC/TBD-associated bone marrow failure (BMF). One report has shown an apparent increase in TL in patients while on treatment with the attenuated androgen danazol. The aim of this study was to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
1
25
0
6
Order By: Relevance
“…La evidencia de múltiples dientes permanentes con disminución de la relación raíz/corona pueden sugerir el diagnóstico de DC (4). Entre otros hallazgos clínicos se encuentran fibrosis pulmonar, e insuficiencia o fibrosis hepática (1)(2)(3)5,7,10). Presentan además un riesgo de 50 veces mayor de la población general de desarrollar tumores hematológicos y sólidos, incluidos el síndrome mielodisplásico, la leucemia mieloide aguda, el linfoma no Hodgkin, el carcinoma de células escamosas de cabeza y cuello, el cáncer de esófago, anogenital, y el carcinoma de células basales, como complicaciones graves (1,2,4,5,8,10).…”
Section: Figura 1 Distrofia Ungueal Y Leucoplasia Oralunclassified
See 2 more Smart Citations
“…La evidencia de múltiples dientes permanentes con disminución de la relación raíz/corona pueden sugerir el diagnóstico de DC (4). Entre otros hallazgos clínicos se encuentran fibrosis pulmonar, e insuficiencia o fibrosis hepática (1)(2)(3)5,7,10). Presentan además un riesgo de 50 veces mayor de la población general de desarrollar tumores hematológicos y sólidos, incluidos el síndrome mielodisplásico, la leucemia mieloide aguda, el linfoma no Hodgkin, el carcinoma de células escamosas de cabeza y cuello, el cáncer de esófago, anogenital, y el carcinoma de células basales, como complicaciones graves (1,2,4,5,8,10).…”
Section: Figura 1 Distrofia Ungueal Y Leucoplasia Oralunclassified
“…Los telómeros, están constituidos por repeticiones de 6 nucleótidos en los extremos de los cromosomas (5). Es un complejo de nucleoproteínas esencial para la estabilidad cromosómica, y se acortan con cada división celular (5,7).…”
Section: Etiopatogenia Y Diagnósticounclassified
See 1 more Smart Citation
“…54 However, a recent retrospective study found no difference in the telomere attrition rates of androgen-treated or untreated patients with dyskeratosis congenita irrespective of the type of androgen therapy used or leukocyte subset evaluated; such data imply a mechanism of clinical response other than androgen-related effects on telomere homeostasis. 55 It remains to be seen whether or not abrogation of telomere length shortening seen in AA (and the foreseeable chromosomal instability) with androgen therapy averts the molecular pathogenesis of clonal evolution.…”
Section: Telomere Homeos Ta S Is Pathologymentioning
confidence: 99%
“…found an increase in TL using qPCR in patients treated with danazol, whereas Khincha et al . did not observe increased TL in danazol‐treated patients when assessed by Flow‐FISH, raising the question of the most appropriate TL measurement technique . Conversely, qPCR provided reproducible data in an idiopathic pulmonary fibrosis (IPF) study, suggesting that qPCR may offer reliable results in experienced hands and under well‐defined conditions, although this will require further investigation.…”
mentioning
confidence: 96%